Clinical significance of CYP2C19 polymorphisms on the metabolism and pharmacokinetics of 11β‐hydroxysteroid dehydrogenase type‐1 inhibitor BMS‐823778. (4th October 2017) - Cheng, Yaofeng; Wang, Lifei; Iacono, Lisa; Zhang, Donglu; Chen, Weiqi; Gong, Jiachang; Humphreys, William Griffith; Gan, Jinping
Abstract : Aims: BMS‐823778 is an inhibitor of 11β‐hydroxysteroid dehydrogenase type‐1, and thus a potential candidate for Type 2 diabetes treatment. Here, we investigated the metabolism and pharmacokinetics of BMS‐823778 to understand its pharmacokinetic variations in early clinical trials. Methods: The metabolism of BMS‐823778 was characterized in multiple in vitro assays. Pharmacokinetics were evaluated in healthy volunteers, prescreened as CYP2C19 extensive metabolizers (EM) or poor metabolizers (PM), with a single oral dose of [ 14 C]BMS‐823778 (10 mg, 80 μCi). Results: Three metabolites (<5%) were identified in human hepatocytes and liver microsomes (HLM) incubations, including two hydroxylated metabolites (M1 and M2) and one glucuronide conjugate (M3). As the most abundant metabolite, M1 was formed mainly through CYP2C19. M1 formation was also correlated with CYP2C19 activities in genotyped HLM. In humans, urinary excretion of dosed radioactivity was significantly higher in EM (68.8%; 95% confidence interval 61.3%, 76.3%) than in PM (47.0%; 43.5%, 50.6%); only small portions (<2%) were present in faeces or bile from both genotypes. In plasma, BMS‐823778 exposure in PM was significantly (5.3‐fold, P  = 0.0097) higher than in EM. Furthermore, total radioactivity exposure was significantly higher ( P  < 0.01) than BMS‐823778 exposure in all groups, indicating the presence of metabolites. M1 was the only metabolite observed in plasma, and much lower in PM. In urine, the amount of M1 and its oxidative metabolite in EM was 7‐fold of that in PM, while more glucuronide conjugates of BMS‐823778 and M1 were excreted in PM. Conclusions: CYP2C19 polymorphisms significantly impacted systemic exposure and metabolism pathways of BMS‐823778 in humans.